Resolving Kashmir: imperatives and solutions. (October 2014) - Baba, Noor Ahmad
The Kashmir problem has existed for over sixty years, since the British colonial rulers left and the subcontinent was partitioned between Pakistan and India, yet the issue continues to be unresolved. The promised plebiscite for the people of Kashmir to decide their future was never held. Various complexities borne out of the continuation of the dispute and divergent claims and positions on the issue still demand urgent attention. For many years, India and Pakistan squared up to one another, testing nuclear arms, amassing troops on the border. But post-Cold War developments, in tandem with their regional implications and a recognition that security threats are changing, have created conditions for rethinking the India-Pakistan relationship and the 'problem' of Kashmir. Today, generally, the traditional preoccupation with national security is giving way to a new discourse of human security and hard borders are giving way to soft borders and development in terms of regional co-operation. On the economic front, China is challenging India and its regional support, whilst India's trade route westward is hampered by lack of access through Pakistan. And these developments, argues the author, could create space for readjusting relations and addressing the future of Kashmir and its people, thousands of whom have lost their lives as a result of the conflict. Since 1947, a variety of solutions from plebiscite and condominium status to a Northern Ireland-style Good Friday Agreement have been put forward, as yet to no avail. Frameworks prepared in the abstract cannot be applied to a complex problem like Kashmir. But there may be lessons to draw on from resolutions of similar conflicts, even if the Kashmir solution has to have its own particular parameters. The challenge for the region is to maximise current opportunities. In this, the international community and the South Asian Association for Regional Cooperation (SAARC) have a role in encouraging the peace process.